Evaluation of Different Doses in Inhaled Therapy: A Comprehensive Analysis - José Luis Lopez-Campos; Rocio Reinoso-Arija; Marta Ferrer Galván; Auxiliadora Romero Falcón; Francisco J. Alvarez-Gutiérrez; Francisco Ortega-Ruiz; Esther Quintana-Gallego (MDPI AG, 2023)
Background. Currently, there is a considerable degree of confusion over the dosage of inhaled medications. Here, we carried out a review of all the doses used for the devices used in inhalation therapy. Methods. We first performed a systematic search of the different inhalation devices included on the July 2023 Spanish Ministry of Health Billing List. We then consulted the Spanish Agency for Medicines and Health Products to find the updated official label and to obtain the information on the exact composition. Results. We identified 90 unique products, of which 22 were long-acting bronchodilators (and combinations thereof) and 68 were products containing inhaled corticosteroids (ICS). Overall, 10 products with bronchodilators and 40 with ICS were marketed with the metered dose, while 11 with bronchodilators and 28 with ICS were marketed with the delivered dose. In addition, in some bronchodilators, the drug was referred to as a type of salt, whereas in others the information referred to the drug itself. Conclusions. Our data show that for each inhaled drug there may be up to four different doses and that the marketed name may refer to any of these. Clinicians must be aware of these different dosages when prescribing inhaled medications.